Outcomes of Teenage Pregnancy in Developing Countries: A Scoping Review - Febrianti, Cindy Putri; Astuti, Andari Wuri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Teenage pregnancy is a health problem that impacts not just physical changes but also psychological, social, and economic ones. These numerous impacts can harm both the health and well-being of teenagers and affect the health quality of a country. This research aimed to point out and explore scientific evidence related to the impact of pregnancy on teenagers in developing countries. The scoping review method from the 2021 PRISMAScR checklist framework was adopted in this review. Pubmed, Wiley Online Library, EBSCO, Proquest, and Grey literature were used as the databases and accessed through the Google Scholar search engine by filtering articles published from 2016 to 2021. There were 10 of the 630 articles screened by inclusion and exclusion criteria found in this review. It showed various impacts, such as physiological, psychological, social, and economic. This review found that the impacts of teenage pregnancy are linked to many factors, including physical changes and all aspects of life lived by teenagers, such as school, work, parenting, and socializing in their neighborhood. Early sexual education must be carried out not just at school but also at home, where the beginning of the educational process happens